2015
DOI: 10.1038/labinvest.2015.74
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin supports human fetal islet-epithelial cell differentiation via p70s6k and promotes vascular formation during transplantation

Abstract: The human fetal pancreas expresses a variety of extracellular matrix (ECM) binding receptors known as integrins. A provisional ECM protein found in blood clots that can bind to integrin receptors and promote β cell function and survival is fibrin. However, its role in support of human fetal pancreatic cells is unknown. We investigated how fibrin promotes human fetal pancreatic cell differentiation in vitro and in vivo. Human fetal pancreata were collected from 15 to 21 weeks of gestation and collagenase digest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
0
7
1
Order By: Relevance
“…Fibrin was selected as the hydrogel of choice due to the fact that it has shown success in islet transplantation studies, facilitates microvessel ingrowth, and has an easy-to-use crosslinking mechanism achieved by combining fibrinogen with thrombin. 51 55 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibrin was selected as the hydrogel of choice due to the fact that it has shown success in islet transplantation studies, facilitates microvessel ingrowth, and has an easy-to-use crosslinking mechanism achieved by combining fibrinogen with thrombin. 51 55 …”
Section: Resultsmentioning
confidence: 99%
“…Fibrin was selected as the hydrogel of choice due to the fact that it has shown success in islet transplantation studies, facilitates microvessel ingrowth, and has an easyto-use crosslinking mechanism achieved by combining fibrinogen with thrombin. [51][52][53][54][55] Rat-sized BVPs were created using rat pancreatic islets coated around decellularized human umbilical arteries (DHUA) that were 1 mm in diameter and 1-1.5 cm in length, with a wall thickness of 300-500 μm. 56,57 Pancreatic islets were isolated from adult rat pancreata using a series of enzymatic digestion steps, and then were coated onto the outer surface of DHUA by combining islets, fibrinogen, and thrombin together into a mold containing the DHUA (Figure 1(b)).…”
Section: Device Creationmentioning
confidence: 99%
“…In the present study, since no metabolically active cells were observed on SDS‐processed bladders, we decided it was not worth performing immunostaining and GSIS with INS‐1 cells seeded on those. Previously, studies have been conducted to characterize INS‐1 cell proliferation and functionality on fibronectin‐coated TCPS, RGD‐coated TCPS, and fibrin 68,71,72 . Here, TCPS was selected as positive control, as it is our established reference for INS‐1 cell attachment and functionality 73 .…”
Section: Resultsmentioning
confidence: 99%
“…Previously, studies have been conducted to characterize INS-1 cell proliferation and functionality on fibronectin-coated TCPS, RGDcoated TCPS, and fibrin. 68,71,72 Here, TCPS was selected as positive control, as it is our established reference for INS-1 cell attachment and functionality. 73 matrices such as MatriStem, Oasis or others could have been an option for instance, but it would be a study on its own, as no study of INS-1 cells on these matrices has been reported.…”
Section: Proliferation Of Ins-1 Cells On Decellularized Bladdersmentioning
confidence: 99%
“…Furthermore, much of the prior research has been focused on cellular encapsulation, which prevents vascularization of the transplanted graft, that causes cellular hypoxia, as oxygen is only delivered to the cells through diffusion, leading to either necrosis or greatly reduced function of transplanted islets [17,18]. A macroporous device would allow vascularization of the graft, improving survival and function and reducing delays in glucose sensing, and can be loaded with fibrin, which is biocompatible and degradable, to further promote β cell survival and function along with host integration and vascularization [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%